Different responses of community temporal stability to nitrogen and phosphorus addition in a non-degraded alpine grassland. (October 2022) - Zong, Ning; Hou, Ge; Shi, Peili; Zhou, Tiancai; Yu, Jialuo; Tian, Jing
Highlights: Both N and N + P increased aboveground biomass, while P addition had no effect. N and/or P treatments decreased community stability, except for low N treatment. The driving mechanisms underlying community stability shifted with nutrient types. Abstract: Fertilization has been widely used in grassland management, but different types of fertilizers may have inconsistent impacts on grassland productivity and stability. However, less is known about the responses of plant community stability and the shifts of driving mechanisms under different fertilizers. We conducted a long-term nitrogen (N) and/or phosphorus (P) addition experiment in an alpine steppe meadow, using two N levels (5 (N5), 10 (N10) g N/m −2 (−|-) year −1 ), one P level (5 g N m −2 year −1, P5) and the combined treatments (N5P5 and N10P5), to examine their effects on community temporal stability and the underlying mechanisms. Both N addition alone and the combined addition significantly increased community aboveground biomass, while P5 did not affect community aboveground biomass. However, only N10, N5P5, and N10P5 decreased annual average species richness, while other treatments showed no pronounced effect. Except for N5, community stability decreased under both N and P additions. The most remarkable finding is that the driving mechanisms underlying community stability shifted with nutrient types. The decrease in species richness induced by N addition decreased community stability. However, the decrease in dominant species asynchrony induced by P addition affected community asynchrony, which contributed to the decrease in community stability. N and P combined addition could additively affect community stability both by species richness and dominant species asynchrony and further community asynchrony. Our results indicate that fertilizer types can alter the regulatory effect of plant diversity on community stability. This study reveals that attention should be paid to the different mechanisms driving community stability under different nutrient types, which provides a scientific basis for alpine grassland management.